Incidence of intraventricular haemorrhage, associated risk factors and short-term outcomes among preterm neonates in a tertiary referral hospital in Kenya - Annette Baine Mwatha; Roseline Ochieng; Rosebella Iseme–Ondiek (PLoS ONE, 2025)
Background Intraventricular hemorrhage (IVH) stands as the predominant cause of brain injury with the incidence increasing with the decrease in birth weight and gestational age. In developed countries, a reduction in IVH incidence by implementing small baby neuroprotective protocols has been reported. The incidence of IVH within our setting is largely unexplored. This study aimed to fill this gap by determining the incidence and associated risk factors of IVH to guide in implementing a small baby neuroprotective protocol that could potentially reduce the incidence of IVH. Method A retrospective cohort study from January 2020 to December 2023 included all Preterm babies with gestation age < 32 weeks or birthweights of ≤1500g admitted to the neonatal intensive care unit (NICU) at The Aga Khan University Hospital, Nairobi. The primary outcome was the occurrence of IVH, while secondary outcomes were associated risk factors and short-term outcomes of IVH. Results A total of 526 babies were admitted to the NICU during the study period. Of these, 135 preterm infants were recruited, and 45 (33.3%) developed IVH, predominantly grade 1 IVH, which occurred predominantly between days 0–28 of life. Logistic regression analysis identified that exposure to antenatal steroids exhibited significantly lower odds of IVH occurrence (AOR 0.075, 95% CI 0.007–0.757). Resuscitation in the NICU had a 3 times higher risk of developing IVH (AOR 2.773, 95% CI 0.867–8.874). Treatment with normal saline bolus and inotropes had 4 times higher odds of IVH occurrence (OR 3.5, 95% CI: 1.043–11.885). A higher mortality rate was observed in preterms with IVH (26.6% vs 13.3%). Post-hemorrhagic ventricular dilation (22% vs 6.7%) and periventricular leukomalacia (20% vs 6.7%) were significantly higher among preterms with IVH. Conclusion The findings elicited from this study lay a foundation for the implementation of neuroprotective protocols which may potentially reduce the magnitude of IVH in this highly vulnerable age group.